Reduction of T-Helper Cell Responses to Recall Antigen Mediated by Codelivery with Peptidoglycan via the Intestinal Nanomineral–Antigen Pathway - Hewitt, Rachel E.; Robertson, Jack; Haas, Carolin T.; Pele, Laetitia C.; Powell, Jonathan J. (Frontiers in Immunology, 2017)
Naturally occurring intestinal nanomineral particles constituently form in the mammalian gut and trap luminal protein and microbial components. These cargo loaded nanominerals are actively scavenged by M cells of intestinal immune follicles, such as Peyer’s patches, and are passed to antigen presenting cells. Using peripheral blood mononuclear cell populations as an in vitro model of nanomineral uptake and antigen presentation we show that monocytes avidly phagocytose nanomineral particles bearing antigen and peptidoglycan, and that the presence of peptidoglycan within particles down-regulates their cell surface MHC class II and up-regulates programmed death receptor ligand 1. Nanomineral delivery of antigen suppresses antigen-specific CD4+ T cells responses, an effect that is enhanced in the presence of peptidoglycan. Blocking the interleukin-10 receptor restores CD4+ T cell responses to antigen co-delivered with peptidoglycan in nanomineral form. Using human intestinal specimens we have shown that the in vivo nanomineral pathway operates in an interleukin-10 rich environment. Consequently the delivery of a dual antigen-peptidoglycan cargo by endogenous nanomineral in vivo is likely to be important in the establishment of intestinal tolerance; whilst their synthetic mimetics present a potential delivery system for therapeutic applications targeting the modulation of Peyer’s patch T cell responses.